Body size, body composition and endometrial cancer risk among postmenopausal women in UK Biobank - Omiyale, W; Allen, NE; Sweetland, S (Wiley, 2020)
Previous studies on the association of adiposity with endometrial cancer risk have mostly used body mass index (BMI) as the main exposure of interest. Whether more precise measures of body fat, such as body fat percentage and fat mass estimated by bioimpedance analyses, are better indicators of risk than BMI is unknown. The role of central adiposity and fat-free mass in endometrial cancer development remains unclear. We used Cox regression models to estimate hazard ratios (HR) and corresponding 95% confidence intervals (CI) for the associations of various measures of body size/composition with the risk of endometrial cancer among 135 110 postmenopausal women enrolled in UK Biobank. During a mean follow up of 6.8 years, 706 endometrial cancers were diagnosed, with a mean age at diagnosis of 65.5 years. The HRs (95% CIs) for endometrial cancer per 1 SD increase in BMI, body fat percentage and fat mass were broadly comparable, being 1.71 (1.61-1.82), 1.92 (1.75-2.11) and 1.73 (1.63-1.85), respectively. There was an indication of positive association between central adiposity, as reflected by waist circumference (HRper 1-SD increase = 1.08, 95% CI: 1.00-1.17) and waist to hip ratio (HRper 1-SD increase = 1.13, 95% CI: 1.01-1.26), and endometrial cancer risk after accounting for BMI. Fat-free mass was not an independent predictor of risk in this cohort. These findings suggest that body fat percentage and fat mass are not better indicators of endometrial cancer risk than BMI. Further studies are needed to establish whether central adiposity contributes to risk beyond overall adiposity.